Søren Kierkegaards »Der Begriff Angst« im Kursunterricht der gymnasialen Oberstufe - v. Kloeden, W. (KIERKEGAARDIANA, 1977)
Søren Kierkegaards »Der Begriff Angst« im Kursunterricht der gymnasialen Oberstufe